Islam Nusantara antara Ortodoksi dan Heterodoksi - Akhiyat Akhiyat (AL-TAHRIR, 2017)
Abstract: Religious style of Indonesia or Islam Nusantara has its own peculiarities. The form that can be found from the different shades of Islamic Archipelago with other countries in the Middle East, especially the Islamic origins of Saudi Arabia, namely in terms of uniqueness of the treasures of the experience and the practice of the Indonesian people as their adherents. It can be said that Islam Nusantara is Islam as moral and moral teachings for its adherents, and not Islam as "ideology" that does not appreciate the understanding of others. Departing from the different shades between Islam Nusantara and Islam with other countries, not separated from the historical background of the existence of cultural experiences of experience and religious belief of its predecessors. Islam Nusantara which has become an important part of adherents in Indonesia, viewed from the aspect of propriety of its adherents, can be categorized as "Islam of humanistic orthodoxy." They in carrying out Islam always maintain its normative religious values, hold to Al-Qur'an and al- Hadith. In addition they also carry out historical teachings, in which the role of spiritual values, inner values (esoteric) in religion, especially the values of human morality has become a very urgent principle in his life. As the rites are at the level of the reality of the life of the people, in every moment of his life rite can not be separated by the name of holding a religious attitude (rite of life)), pleading for a supernatural (unseen) outside, in religious language begging for help The Almighty, the God of nature.الملخص:  إن الأنماط الدينية لمجتمع  إندونيسيا أو ما يسمى بالإسلام نوسانتارا له خصوصية خاصة. وكان الشكل الذي يمكن العثور عليه من ظلال مختلف الإسلام نوسانتارا بالنسبة إلى دول أخرى في الشرق الأوسط، ولاسيما من أصل الدولة الإسلامية في المملكة العربية السعودية، وهي من حيث تفرد كنوز التجربة وممارسة الشعب الإندونيسية كأتباعهم. ويمكن القول أن الإسلام نوسانتارا هو الإسلام كما هو تعاليم الأخلاقية والسلوكية لأتباعها، وليس الإسلام كما أنه "أيديولوجية" التي لا يقدر فهم الآخرين. إنطلاقا من ظلال مختلفة بين الإسلام نوسانتارا والإسلام مع بلدان أخرى، فلا ينفصل عن الخلفية التاريخية من وجود الخبرات الثقافية من الخبرة والمعتقدات الدينية من أسابقها. و أصبح الإسلام نوسانتارا جزءا ضروريا من أتباع في اندونيسيا، نظرا إلى جانب مدى ملاءمة أتباعها، ويمكن تصنيفها على أنها "الإسلام من الأرثوذكسية الإنسانية". إنهم في تنفيذ الإسلام يحافظون دائما على القيم الدينية المعيارية، ويعتمدون على القرآن والحديث. وبالإضافة إلى ذلك، فإنهم يقومون أيضا بتعاليم تاريخية، فأصبح فيها دور القيم الروحية والقيم الداخلية (الباطنية) في الدين، وخاصة لقيم الأخلاق الإنسانية التي يصير مبدأ هاما في الحياة. وكما أن الشعائر الدينية التي هي على مستوى واقع حياة المجتمع، في كل لحظة من حياته كانت لا يمكن فصلها عن طريقة عقد موقف ديني (شعائر الحياة))، والطلب من القوة الخارقة (غير مرئي) في الخارج، في اللغة الدينية يقال الطلب من مساعدة سبحانه وتعالى، خالق العالم.Abstrak: Corak keberagamaan masyarakat Indonesia atau Islam Nusantara telah memiliki kekhasan tersendiri. Bentuk perbedaan corak Islam Nusantara dengan negara-negara lain di Timur Tengah, terutama negara asal Islam, Arab Saudi, adalah dari segi kekhasan khasanah pengalaman dan pengamalan batin masyarakat Indonesia sebagai pemeluknya. Dapat dikatakan bahwa Islam Nusantara adalah Islam sebagai ajaran akhlak dan moral bagi pemeluknya, dan bukan Islam sebagai “ideologi” yang tidak menghargai pemahaman kelompok lain. Perbedaan corak antara Islam Nusantara dengan Islam di negara lain disebabkan oleh belakang historis keberadaan tradisi pengalaman budaya dan kepercayaan religiusitas para pendahulunya. Islam Nusantara yang telah menjadi bagian penting pemeluknya di Indonesia, dilihat dari segi kepatutan masyarakat penganutnya, dapat dikategorikan sebagai “Islam ortodoksi humanis.” Dalam menjalankan Islam, mereka senantiasa masih mempertahankan nilai-nilai normatif keberagamaannya, berpegang kepada al-Qur’an dan al-Hadis. Di samping itu, mereka juga menjalankan ajaran historis, yang mana peran nilai-nilai spiritualitas, nilai-nilai batiniah (esoteris) dalam agama, terutama nilai-nilai moralitas kemanusiaan telah menjadi prinsip yang sangat urgen dalam kehidupan. Sebagaimana ritus-ritus dalam realitas kehidupan masyarakatnya, pada setiap momen ritus kehidupannya tidak lepas dengan yang namanya mengadakan suatu sikap religiusitas (upacara ritus kehidupan), memohon pertolongan kepada sesuatu kekuatan (ghaib) di luar dirinya, dalam bahasa agama memohon pertolongan kepada Sang Maha Kuasa, Tuhan Pencipta alam.